Social exclusion, health and hidden homelessness. (October 2016) - Watson, J.; Crawley, J.; Kane, D.
Abstract: Objectives: Homelessness and poverty are extreme forms of social exclusion which extend beyond the lack of physical or material needs. The purpose of this study was to explore and expand the concept of social exclusion within the social determinants of health perspective – to understand how the social environment, health behaviours and health status are associated with material and social deprivation. Study design: Fundamental qualitative description with tones of focused ethnography. Methods: Participants who identified as hidden homeless described their everyday living conditions and how these everyday conditions were impacted and influenced by their social environments, coping/health behaviours and current health status. Research Ethics Board approval was granted and informed consents were obtained from 21 participants prior to the completion of individual interviews. Results: Qualitative content analysis examined the descriptions of men and women experiencing hidden homelessness. Participants described the 'lack of quality social interactions and supports' and their 'daily struggles of street life'. They also shared the 'pain of addiction' and how coping strategies influenced health. Participants were hopeful that their insights would 'better the health of homeless people' by helping shape public policy and funding of community resources that would reduce barriers and improve overall health. Conclusions: Health professionals who understand health behaviours as coping mechanisms for poor quality social environments can provide more comprehensive and holistic care. The findings of this study can be used to support the importance of housing as a key factor in the health and well-being of people experiencing poverty, homelessness and social exclusion; and consequently, reinforces the need for a national housing strategy.